Effects of oxygen on the Maillard reaction of lactose - Trang, Vu Thu (Vietnam Journal of Science and Technology, 2015)
The effects of dissolved oxygen (DO) on the Maillardreaction of lactose were investigated. In the model solution of lactose andbutylamine, the aminoreductone (AR), Galactose (Gal) concentration, Maillardreaction products, in deaerated sample were significantly higher than that innon-deaerated sample. The browning of deaerated sample at 420nm which indicatedthe formation of melanoidin, Maillard reaction products, was also higher thanthat in in non-deaerated sample. The decrease in the oxygen concentration inthe samples during heating at different heating conditions was recognizedcorrelated with the formation of Maillard reaction products (AR, Gal andbrowning compounds). Our results might give more insight in the discovery ofMaillard reactions in food because it suggested tendency of the Maillardreaction during food processing base on the control of oxygen content exceptingfor the initial constituents and reaction conditions. During processing, themanufacturer should concern to the participation of oxygen to receive thehighest quality and nutritive value of the final products.